Students’ Mathematical Reasoning Ability in Junior High School Mathematics Learning with Contextual Reasoning - Hadi, Samsul; Rahman, Abdur; Gafur, Abdul (Journal of Education and Social Science, 2024)
The purpose of this study was to provide a comprehensive description of the mathematical reasoning abilities of students in elementary mathematics learning within the context of reasoning. This research employed a qualitative approach with a case study design involving 35 first-semester students of the Elementary School Teacher Education Program (PGSMP) in the 2021–2022 academic year, consisting of 12 female and 23 male participants. Data were collected using both test and non-test techniques, including interviews, classroom observations, questionnaires, and documentation studies, in order to obtain a holistic understanding of the students’ reasoning abilities. The analysis focused on identifying indicators of mathematical reasoning such as the ability to make logical connections, construct arguments, provide justifications, identify patterns, and draw conclusions. The findings revealed that the mathematical reasoning abilities of the PGSMP students in the context of elementary mathematics learning were generally categorized as good. Furthermore, the study highlights the importance of integrating reasoning-oriented tasks in mathematics learning to strengthen students’ critical thinking and problem-solving skills. These results suggest that mathematics educators should continue to emphasize reasoning in instructional practices, as it not only enhances students’ cognitive development but also prepares them to apply mathematical knowledge in real-world contexts.